2021
DOI: 10.3390/medicina57060583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 Pandemic-Related Stress among Frontline Medical Personnel in Daegu City, Korea

Abstract: Background and Objectives: Frontline medical staff usually experience high levels of stress, which could greatly impact their work output. We conducted a survey to investigate the level of stress and its association with job types, work departments, and medical centers among COVID-19 pandemic frontline medical personnel. Materials and Methods: We conducted a cross-sectional survey using a self-administered questionnaire among 307 frontline medical staff who cared for COVID-19 patients in Daegu city. We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
4
2
0
Order By: Relevance
“…Consistent with the findings of previous studies, we found that nursing professionals were more likely to feel stress or anxiety than other health care workers [ 15 , 16 , 20 , 29 , 30 ]. Nursing professionals are in crisis as they care for patients with infections, experience fear of infectious diseases, insufficient isolation-patient-care-systems, and ethical dilemmas [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of previous studies, we found that nursing professionals were more likely to feel stress or anxiety than other health care workers [ 15 , 16 , 20 , 29 , 30 ]. Nursing professionals are in crisis as they care for patients with infections, experience fear of infectious diseases, insufficient isolation-patient-care-systems, and ethical dilemmas [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies, we also found that nursing professionals were more likely to feel stress or anxiety than other healthcare workers [14,15,19,27,28]. Nursing professionals are in crisis as they care for infected patients but experience fear of infectious diseases, insufficient isolation-patient-care-systems, and ethical dilemmas [29].…”
Section: Discussionsupporting
confidence: 89%
“…This view is consistent with our study and the studies by Alyahya et al [15] and Farraji et al [16]. However, Romano et al [17] and Shin et al [18] also reported that the sociodemographic characteristics and work stress of nurses were correlated.…”
Section: Discussionsupporting
confidence: 93%